PAULO FREIRE’S CULTURAL IDENTITY AND EDUCATION: REFLECTIONS AROUND THESE CONCEPTS - Estupiñán Quiñones, Norman; Agudelo Cely, Nubia (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
This paper presents an interpretation about the concepts of cultural identity and education based on texts by Paulo Freire; educational relations emerging from the school between «educator» and «student», a link that in many cases is marked by ignorance and the denial of youth cultures, are highlighted.This document is part of the reference framework built through the research project called, «Meaning and significance of multiculturalism», which is based on the view that education should respond to new ways of knowing, feeling and building individual and social identities.